2020
DOI: 10.3389/fonc.2020.595832
|View full text |Cite
|
Sign up to set email alerts
|

ZAP-70 Shapes the Immune Microenvironment in B Cell Malignancies

Abstract: Zeta-chain-associated protein kinase-70 (ZAP-70) is a tyrosine kinase mainly expressed in T cells, NK cells and a subset of B cells. Primarily it functions in T cell receptor (TCR) activation through its tyrosine kinase activity. Aberrant expression of ZAP-70 has been evidenced in different B cell malignancies, with high expression of ZAP-70 in a subset of patients with Chronic Lymphocytic Leukemia (CLL), associating with unfavorable disease outcomes. Previous studies to understand the mechanisms underlying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 70 publications
(93 reference statements)
0
14
0
Order By: Relevance
“…Chen et al demonstrated that ZAP70 could promote cell survival, microenvironment interactions, protein synthesis and further drive disease progression in chronic lymphocytic leukemia cells (Chen et al, 2021). ZAP-70 could also shape the immune microenvironment in B cell malignancies ( Chen et al, 2020 ). Liu et al proposed that ZAP70-deficiency may improve reverse cholesterol transport and decrease the inflammatory response of T cells ( Liu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al demonstrated that ZAP70 could promote cell survival, microenvironment interactions, protein synthesis and further drive disease progression in chronic lymphocytic leukemia cells (Chen et al, 2021). ZAP-70 could also shape the immune microenvironment in B cell malignancies ( Chen et al, 2020 ). Liu et al proposed that ZAP70-deficiency may improve reverse cholesterol transport and decrease the inflammatory response of T cells ( Liu et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, ZAP−70 may participate in BCR signalling by limiting the ability of BCR to induce negative B-cell selection and cell death [ 109 ]. Additionally, ZAP−70 may regulate BCR signalling via its kinase activity or as a scaffold protein recruiting the other tyrosine kinases [ 110 ]. Given that RhoH is widely known to regulate ZAP−70 activation, it may also be implicated in SLE.…”
Section: Deregulation Of Rhoh In Diseasesmentioning
confidence: 99%
“…The activation domain used in the structure of CARs has the critical role of T cell activation upon target antigen encountering and it is mostly derived from the CD3ζ part of the T cell receptor (TCR) CD3 complex ( 13 ). However, other activation domains that have been used include FcϵRIγ, the ζ-chain of TCR-associated protein kinase 70 kDa (ZAP70), and DAP12 ( 13 17 ). The early CAR T cells (termed “first-generation CARs”) did not have any co-stimulatory domain and did not show promising antitumor efficacy mainly due to the lack of adequate persistence and activation ( 18 ).…”
Section: Introductionmentioning
confidence: 99%